THE EFFECTS OF PAPAYA LEAVES JELLY IN LIPID PROFILE AMONG OVERWEIGHT WOMEN - Nissa, Choirun; Pratiwi, Syafira Noor; Majidah, Siti; Rahma, Nadia; Paramastuti, Ratih; Hindarta, Nadhea Alriessyanne; Syauqy, Ahmad; Wijayanti, Hartanti Sandi; Afifah, Diana Nur (Journal of Nutrition College, 2020)
Background : Insulin resistance that occurred in diabetic state could promote endothelial dysfunction which lead to metabolic disease in obese subjects. Although several studies showed papaya leaves had antidiabetic and antihyperlipidemic agent, the effect of papaya leaves jelly is rarely studied on lipid profiles among overweight women.Objectives : We aimed to examine the effect of papaya leaves jelly on lipid profiles in women with overweight. Methods : This study was a pre-posttest controlled group design with both of the groups were overweight. The treatment group consumed papayq leaves jelly with 24.6 grams papaya leaves jelly that contains 182.4 mg chlorophyll, while the control group consumed 24.6 grams jelly with green dye for 20 days in a row. Three-day recall in three non-consecutive days and physical activity using International Physical Activity (IPAQ) were taken three times. Fasting blood sugar was measured using Glucose Oxidase Phenol 4-Aminophenazone (GODPAP). LDL, HDL, total cholesterol, triglyceride levels were measured using Cholesterol Oxidase Para Aminophenazone (CHOD-PAP). Statistical analysis using Paired t-test was used within group, while Independent t-test and Mann-Whitney were used in between groups. Papaya leaves jelly effects on lipid profiles was analyzed using multiple linear regression after considering energy, protein, fat, and carbohydrate intakes. Results : Triglyceride levels was reduced significantly (p=0.014) in the treatment group despite there were no differences in triglyceride (p= 0.407), LDL (p= 0.923), HDL (p= 0.749) and total cholesterol (p= 0.277) between 2 groups. Conclusion : Papaya leaves jelly consumption could lower triglyceride levels significantly in the treatment group.